Analysis of the equilibrium equations of a discrete computational model of the soil half space - Прусов, Д.Е. (Proceedings of National Aviation University (archive), 2009)
The analysis of equilibrium equation of discrete design model of soil semispace is realized to develop the special algorithm for nonlinear equations system solution of two-dimensional problem using continuation method by perturbation parameter, Newton-Kantorovich method, and continuation method by plastically deformation evolution.